Development of a low-cost aseismic base isolation device for protection of structural systems from damaging effects of earthquakes - Kesti, Mustafa Gökhan. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2009., 2009)
Due to the killing thousands of people in the twentieth century and seismicity of our country, earthquakes are one of the most important natural hazards for our country. Therefore the earthquake resistance of structural system plays central role for earthquake protection. This M.Sc. thesis research’s concern is to illustrate some base isolation techniques and to propose a base isolation device to improve the earthquake resistance of structural systems. The so-called Ball-N-Cone (BNC) aseismic base isolation device is experimentally studied and results are given.
Keywords: Earthquake resistant design.; Buildings -- Earthquake effects.; Earthquake engineering.